Tratamento de Efluente de Microcervejaria por Coagulação e Filtração Rápida - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Breweries produce a large amount of effluents with a high organic matter load that, if not treated properly, can contaminate the environment. This study investigated the simultaneous coagulation and rapid filtration processes in the treatment of microbrewery effluents, evaluating a Double Filtration (DF) and Triple Filtration (TF) pilot unit for the post-treatment of anaerobic decant digester effluents. To monitor the treatment stages, analyses were performed on Apparent Color, True Color, Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), Total Phenols, Total Phosphorus (PT), Ammoniacal Nitrogen (N-NH3), Nitrate (NO3 - ), Nitrite (NO2 - ), Total Kjeldahl Nitrogen (NTK), Total Dissolved Solids (TDS), TDS - fixed, TDS - volatile, Total Suspended Solids (TSS), TDS - fixed, TDS - volatile, Total Solids (TS), TDS - fixed, TDS - volatile and Turbidity. To determine the best dosages of Ferric Chloride (FeCl3), Polyaluminum Chloride (PAC) and Tannins (TAN) coagulants in relation to turbidity and color removal, coagulation diagrams were constructed in Jar Test, varying the concentrations from 50 mg L-1 to 400 mg L-1 at different pH values from 4.5 to 8.0. After obtaining the best coagulation conditions, rapid filtration studies were carried out at a rate of 120 m3 .m2 .day-1 using double filtration (DF) with gravel and sand and triple filtration (TF) with gravel, sand, coal and zeolite. The treatment tests in the filters were carried out with sample collection at intervals of 30, 60 and 90 minutes to measure their efficiency and verify whether they maintained the removal capacity of the physicochemical parameters throughout the coagulation/filtration process. Studies of iodine number in activated carbon and cation exchange capacity (CEC) were carried out to estimate the loss of efficiency of these filters in relation to the filtered volume. The tests showed that the best results were obtained at pH close to 7.0 for the three coagulants. It was found that for the passage of microbrewery effluents in the DF and TF system, it was necessary to correct the coagulant concentrations due to oscillations in the color and turbidity parameters, thus the concentrations of 130 mg L-1 of FeCl3, 95 mg L-1 of PAC and 100 mg L-1 TAN were necessary. After 30 minutes of coagulation and filtration, the results indicated significant reductions in the analyzed parameters. For FeCl3, PAC and TAN, the apparent color decreased between 89% and 92%, while the turbidity ranged from 92% to 93%. Total dissolved solids (TDS) were reduced between 84% and 86%, total suspended solids (TSS) between 78% and 87%, and total solids (TS) between 83% and 88%. BOD and COD parameters showed reductions of 25% to 31%, while ammonium compounds (N-NH3) and total nitrogen (NTK) had reductions between 47% to 49% and 52%, respectively. Total phosphorus (TP) showed a reduction of 64% to 68%, and total phenols, from 77% to 78%. With coagulation followed by double or triple filtration, the results were even more expressive. The apparent color was reduced by up to 97%, TDS and TSS reached reductions of 94%, while ST reached 95%. Turbidity decreased by up to 98%, and BOD5 and COD reductions exceeded 55% and 64%, respectively. N-NH3 and NTK showed reductions of up to 69% and 74%, while phosphorus and phenols reached values of 99% and 100%. Regarding the use of coal and zeolite in the TF, it was found that after the treatment of 1,500 L, there was a reduction of 5.38% in the adsorption capacity of activated carbon and of 2.95% in the cation exchange capacity of clinoptilolite. Regarding the performance of the coagulants in the removal of the physical- chemical parameters, it was observed that PAC and tannins presented similar results in the Jar Test tests (construction of the coagulation diagrams), however, in the coagulation stage followed by DF and TF, the TAN coagulant obtained, in general, the best performance, achieving the best results. For the removal of all the parameters studied, the proposed system was highly efficient, meeting the disposal criteria of the current legislation, with the exception of BOD and COD. It is concluded that the use of coagulation followed by rapid filtration can be a promising technique in the post-treatment of brewery effluents, provided that a more efficient pre-treatment is carried out.
Keywords: Filtração Rápida; Efluentes de Microcervejaria; Coagulação Química; Cloreto Férrico; PAC e Taninos; Rapid Filtration; Microbrewery Effluents; Chemical Coagulation; Ferric Chloride; PAC and Tannins; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA